2017
DOI: 10.1111/acel.12643
|View full text |Cite
|
Sign up to set email alerts
|

Serpine 1 induces alveolar type II cell senescence through activating p53‐p21‐Rb pathway in fibrotic lung disease

Abstract: SummarySenescence of alveolar type 2 (ATII) cells, progenitors of the alveolar epithelium, is implicated in the pathogeneses of idiopathic pulmonary fibrosis (IPF), an aging‐related progressive fatal lung disorder with unknown etiology. The mechanism underlying ATII cell senescence in fibrotic lung diseases, however, remains poorly understood. In this study, we report that ATII cells in IPF lungs express higher levels of serpine 1, also known as plasminogen activator inhibitor 1 (PAI‐1), and cell senescence ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
134
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(144 citation statements)
references
References 44 publications
9
134
1
Order By: Relevance
“…Furthermore, recent studies using scRNA-Seq approaches have reinforced the importance of aberrant Wnt activation in the ATII cells within the fibrotic lungs (48,50). Wnt/β-catenin signaling is dysregulated in the aged lung and promotes senescence, and a pathogenic feature of reprogrammed fibrotic lung epithelial cells is cellular senescence (8,9,48,60,61). Altogether, these findings suggest that aberrant signaling through this pathway can promote lung fibrosis via initiation of cellular senescence.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Furthermore, recent studies using scRNA-Seq approaches have reinforced the importance of aberrant Wnt activation in the ATII cells within the fibrotic lungs (48,50). Wnt/β-catenin signaling is dysregulated in the aged lung and promotes senescence, and a pathogenic feature of reprogrammed fibrotic lung epithelial cells is cellular senescence (8,9,48,60,61). Altogether, these findings suggest that aberrant signaling through this pathway can promote lung fibrosis via initiation of cellular senescence.…”
Section: Discussionmentioning
confidence: 92%
“…Although the abnormal fibroproliferation that occurs in IPF involves a complex interplay between parenchymal and immune cells, the epithelial barrier has a fundamental role, particularly in early events that lead to lung fibrosis (3). Recently, senescence or depletion of alveolar epithelial cells has been implicated in the pathogenesis of lung fibrosis (4)(5)(6)(7)(8)(9). In addition, several epithelial-expressed genes have been found to confer a risk for the development of pulmonary fibrosis (e.g., MUC5B, SFTPC, SFTPA2, ABCA), further supporting dysfunctional alveolar epithelium as a sentinel event in the development of fibrosis (10).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, Jiang et al . showed that Serpine1 promotes senescence of alveolar type II cells by inducing p53-p21-Rb cell cycle repression pathway in lung disease 66 . Increased expression of Serpine1 in older air vs. younger air-exposed mice suggests that Serpine1 upregulation could mediate cellular senescence of pulmonary cells as the mice age.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of the p53 pathway in the AEC2s of IPF lungs is also associated with high levels of PAI1. Deletion of PAI1 in AEC2s in mice protected these cells from bleomycin-induced senescence 125 . Moreover, a small molecule PAI1 inhibitor (TM5275) blocked fibrosis in mice treated with bleomycin and protected AEC2s from senescence 126 .…”
Section: Ageing Mechanisms and Novel Therapiesmentioning
confidence: 97%